Effect of Dietary Fish Meal Replacement by Poultry By-Product Meal with Different Grain Source and Enzyme Supplementation on Performance, Feces Recovery, Body Composition and Nutrient Balance of Nile Tilapia - Soltan, M.A. (Pakistan Journal of Nutrition, 2009)
The efficacy of replacing Fish Meal (FM) with Poultry By-product Meal (PBM) in Nile tilapia diets on an ideal protein basis with different grain sources and enzyme supplementation was evaluated under condition of cement pond culture. An experimental diet was formulated contain 30% crude protein, 5% ether extract and 3355 Kcal ME/Kg. Four other diets were formulated to be isonitrogenous and isocaloric as the basal diet No. 1, in which FM protein was substituted completely by PBM protein (Basal diet No. 2), while diet No. 3, 4 and 5 sorghum grain replaced 100% of wheat grain (w/w) or 100% of corn grain or 50% of both wheat and corn for the three diets respectively. The fish experimental diets were fed to the fish without or with enzyme supplementation. Statistical analysis of data revealed that inclusion of PBM instead of FM with wheat or sorghum grain plus corn (group 2 and 3) in Nile tilapia diet had no significant (p>0.05) effect on Body Weight (BW), Daily Body Gain (DBG), Daily Feed Intake (DFI), Feed Conversion Ratio (FCR), Protein Efficiency Ratio (PER) and Efficiency of Energy Utilization (EEU) when compared with the control. While corn replacement by sorghum (group 4) or 50% of both corn and wheat by sorghum (group 5) had no effect on DFI, but significantly (p0.05) affected when FM replaced by PBM with different grain sources. Carcass chemical composition data indicated that there is no significant effect of different experimental diets on fish body dry matter, organic matter, crude protein and carbohydrate and phosphorus contents. PBM as FM alternatives has a high potential as feed ingredients replacing FM. Nutrients balances and fecal recovery data showed that PBM with corn + wheat or corn + sorghum results in good fish performance for a similar replacement of FM on protein percent basis. However, they result as well in slightly higher waste loads, in particular of N and C to the system. Sorghum grain as alternative to corn (weight/weight) results in lower fish production and higher nutrient fecal and non fecal losses and prefer to rejected because it has a negative impact on the system. Moreover, enzyme supplementation highly improved the fish performance, nutrient digestibility, carcass traits and fecal recovery and reduces the excessive losses of the nutrient to the environment.